Cytotoxicity and biocompatibility of Meropenem-loaded graphene oxide and its antibacterial effects against carbapenem-resistant Gram-negative bacteria - Mohammad Yousef Memar; Yalda Rahbar Saadat; Solmaz Maleki Dizaj; Mina Yekani; Seyyedeh Mina Hejazian; Bahram Niknafs; Sepideh Zununi Vahed; Simin Sharifi (Elsevier, 2023)
The rising prevalence of multidrug-resistant (MDR) bacteria, mainly Gram-negative bacteria, challenges their effective treatment. Graphene oxide (GO) represents antibacterial activities; however, the synergistic effect of GO with conventional antibiotics remains unclarified. Here, meropenem-loaded GO (Mrp-GO) was prepared and its physicochemical and biocompatibility properties along with its inhibitory effect against carbapenem-resistant Gram-negative bacteria were evaluated. Cytotoxicity of Mrp-GO on human bone marrow-derived mesenchymal stem cells (hBM-MSCs) was examined as well. The prepared nanoparticles had suitable and acceptable physicochemical properties. The antibacterial activity of Mrp-GO increased in comparison to the GO and Mrp alone. Moreover, the Mrp-GO had low hemolytic effects at the concentrations required for bacterial inhibition. The cell viability of hBM-MSCs at toxic Mrp-GO concentrations for bacterial isolates was almost 90-100%. The combination of nanostructure and conventional antibiotics can be a promising treatment modality against carbapenem-resistant Gram-negative bacteria.